Ανασκαφή νεολιθικού οικισμού Θέρμης: ανασκαφική περίοδος 1987 - Γραμμένος, Δ. Β.; Παππά, Μαρία; Ούρεμ-Κώτσος, Ντ.; Σκουρτοπούλου, Κατερίνα; Γιαννούλη, Ευτ. Γ.; Τσιγαρίδα, Μπεττίνα (Μακεδονικά, 1989)
No Abstract